A Comprehensive Spatial Mapping of Muscle Synergies in Highly Variable Upper-Limb Movements of Healthy Subjects - Scano, Alessandro; Dardari, Luca; Molteni, Franco; Giberti, Hermes; Tosatti, Lorenzo Molinari; d’Avella, Andrea (Frontiers in Physiology, 2019)
Abstract Background: Recently, muscle synergy analysis has become a standard methodology for extracting coordination patterns from electromyographic (EMG) signals, and for the evaluation of motor control strategies in many contexts. Most previous studies have characterized upper-limb muscle synergies across a limited set of reaching movements. With the aim of future uses in motor control, rehabilitation and other fields, this study provides a comprehensive characterization of muscle synergies in a large set of upper-limb tasks and considers subjective and environmental variability. Methods: 16 healthy subjects performed upper-limb hand exploration tasks and point-to-point movements in a comprehensive mapping of the upper-limb workspace, which was divided into several sectors (Namely: Frontal, Right, Left, Horizontal and Up). EMGs from representative upper-limb muscles and kinematics were recorded to extract muscle synergies and explore the composition, repeatability and similarity of spatial synergies across subjects and movement directions, in a context of high variability of motion. Results: Even in a context of high variability, a reduced set of muscle synergies may reconstruct the original EMG envelopes. Composition, repeatability and similarity of synergies were found to be shared across subjects and sectors, but with some dependence on the choice of the experimental design and the parameters for the data pre-processing. Conclusions: Extending the results of previous studies on a smaller set of conditions, a limited number of muscle synergies underlie the execution of a large variety of upper-limb tasks. However, the considered spatial domain and the variability seem to influence the number and composition of muscle synergies. Such detailed characterization of the modular organization of the muscle patterns for upper-limb control in a large variety of tasks may provide a useful reference for studies on motor control, rehabilitation, industrial applications and sports.